PERSONIFICATION AND PROMINENCE IN FOREIGN REPORTING ON THE EXAMPLE OF LATIN AMERICA’S NEWS COVERAGE IN THE GERMAN PRESS - Cazzamatta, Regina (Brazilian journalism research, 2020)
This paper aims at reassessing through quantitative content analysis the role of the factors “personification” and “prominence” in the foreign reporting, using the news coverage of Latin America in the German quality press as a case study. The corpus comprises 3.831 news articles published between January 2000 and December 2014 in market-leading media outlets: the dailies Süddeutsche Zeitung (SZ), the Frankfurter Allgemeine Zeitung (FAZ), the alternative tageszeitung (taz) and, additionally, the weekly Der Spiegel, the most relevant political magazine in the country. The factors have similar importance among the publications, although the FAZ shows the less personified and the most elitist coverage, while Der Spiegel exhibits the most vigorous intensity of personification. Besides, under the analysed types of individuals, the press tends to depict celebrities and politicians, mostly from the executive, in a more personified way. Lastly, countries against the Washington consensus and with a high degree of political coverage are more inclined to present the substantial intensity of both factors. O objetivo desse artigo é reavaliar, por meio da análise quantitativa de conteúdo, o papel dos fatores “personificação” e “proeminência” nas coberturas internacionais, utilizando como estudo de caso a cobertura noticiosa da América Latina na imprensa de qualidade alemã. O corpus engloba 3.831 artigos publicados entre janeiro de 2000 e dezembro de 2014 em periódicos líderes de mercado: o Süddeutsche Zeitung (SZ), o Frankfurter Allgemeine Zeitung (FAZ), o alternativo tageszeitung (taz) e, adicionalmente, o semanário Der Spiegel, a revista política mais relevante da Alemanha. Os fatores têm pesos semelhante entre as publicações, embora o FAZ tenha uma cobertura menos personificada e mais elitista, enquanto a Der Spiegel possui uma intensidade de personificação mais marcante. Além disso, em relação aos tipos de indivíduos analisados, a imprensa tende a retratar celebridades e políticos, principalmente do executivo, de uma maneira mais personificada. Por fim, os países contra o consenso de Washington e/ou com um alto grau de cobertura política estão mais inclinados a apresentar uma maior intensidade de ambos os fatores. El objetivo de este trabajo es reevaluar, a través del análisis cuantitativo de contenido, el papel de los factores “personificación” y “prominencia” en la cobertura internacional, utilizando como caso de estudio la cobertura de noticias de América Latina en la prensa alemana de calidad. El corpus comprende 3.831 artículos publicados entre enero de 2000 y diciembre de 2014 en los principales periódicos: Süddeutsche Zeitung (SZ), Frankfurter Allgemeine Zeitung (FAZ), el tageszeitung (taz) alternativo y, además, el semanario Der Spiegel, La revista política más relevante de Alemania. Los factores tienen pesos similares en todas las publicaciones, aunque FAZ tiene una cobertura menos personificada y más elitista, mientras que Der Spiegel tiene una intensidad de personificación más marcada. Además, en relación con los tipos de individuos analizados, la prensa tiende a retratar a las celebridades y los políticos, especialmente el ejecutivo, de una manera más personificada. Finalmente, los países en contra del consenso de Washington y / o con un alto grado de cobertura política son más propensos a tener una mayor intensidad de ambos factores.